MR Digital Subtraction Angiography of Cerebral Arteriovenous Malformations - Tsuchiya, Kazuhiro; Katase, Shichiro; Yoshino, Ayako; Hachiya, Junichi (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: Although phase-contrast MR angiography provides some information regarding hemodynamics of cerebral arteriovenous malformations (AVMs), most conventional MR angiographic techniques have not been helpful in this respect. We attempted to determine the value of MR digital subtraction angiography (DSA) in assessing AVM hemodynamics.METHODS: We developed an MR DSA technique by combining rapid thick-section T1-weighted imaging with a bolus injection of contrast material. The temporal resolution was 0.56 to 0.61 seconds per scan. MR DSA images obtained from 14 patients with AVMs were reviewed. Anatomic depiction of each component of the AVM was rated using a four-point grading scale (excellent = 3, good = 2, fair = 1, poor = 0) to compare conventional vs MR angiograms.RESULTS: We were able to obtain serial images in which passage of contrast material was evident within the AVM, although the sequence we used allowed images to be obtained in only one projection. The average score for feeders, nidi, and drainers was 1.6, 2.4, and 2.3, respectively, with an overall average of 2.1.CONCLUSION: The spatial resolution of our technique may fall below the level needed for identification of small vascular components of an AVM. Additionally, the limited slab may restrict application of the technique to assessment of large or very small AVMs. MR DSA, however, can show the hemodynamics of AVMs and may serve as a supplement to conventional MR imaging in the diagnosis of cerebral AVMs.